(3EQTGO GdSGFd Edi CUhd GdeSGFds - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg aEf GdhSGFd JJTQa HTQa ebGUOgG hJdJMb HgG ai ebGeGJ CMcGegG hEf ef CYXe GdebGUO GdTQYjg s
(3BNQgG (B:s
(3hCSGd Gddg GdYXje GdhgGH Gdbhi GdQMje GdJhGH Cf jhabfG ddYed hjYUefG ef GdRjZ hGdPdd s
(3ajgG QShe cKjQgs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs